The influence of student’s mathematical beliefs on metacognitive skills in solving mathematical problem - Mega Suliani; Dwi Juniati; Agung Lukito (Institute of Advanced Engineering and Science, 2024)
The current research aimed to understand the effect of mathematical beliefs of middle school students on their metacognitive skills in solving mathematical problems. In examining the matter, the study utilized a mixed method. In the first step, a linear regression test was utilized to determine the effect of belief on students’ metacognitive skills in solving geometry problems. Furthermore, a qualitative approach was used to compare the metacognitive skills of high and low-belief students. This study involved 72 middle school students sitting in the 8th grade at Tarakan 1 State Junior High School. Based on the linear regression results, it is known that students’ beliefs positively influenced their metacognitive skills in solving geometric problems. Furthermore, it was found that when both selected subjects with high and low beliefs started solving the problems, they started by planning. Then, they monitored what they had done, but there were differences in evaluating the solutions. Additionally, students who believe strongly in problem solving will be more aware of what they are thinking and thus have an impact on improving their learning outcomes.